Control of swine diseases by slaughterhouse activities : epidemiological studies - Tuovinen, Veikko ([V. K. Tuovinen], 1994)
Summary.
Keywords: Animal health; bekämpning; slakterier; smittsamma sjukdomar; svinhus; svin; köttindustri; köttkontroll; epidemiologi; djursjukdomar; veterinärvård; livsmedelshygien; torjunta; teurastamot; tartuntataudit; sikalat; sika; lihateollisuus; lihantarkastus; epidemiologia; eläintaudit; eläinlääkintä; elintarvikehygienia; Epidemiology; Suomi; Finland